PENGARUH PENGOPERASIAN AIR CONDITIONER TERHADAP KUALITAS TEGANGAN DAN ARUS GERBONG KERETA K3 BUATAN PT INKA - Putra, Ade Mahendra Darma; Hasanah, Rini Nur; Wibawa, Unggul (Jurnal Mahasiswa TEUB, 2024)
One device that is a nonlinear load is AC (Air Conditioner) or air conditioner. This can happen because of the use of induction motors in AC which work using the principles of electromagnetic induction so that they have saturation properties or conditions where the current is not proportional to the voltage. In the manufacture of train carriages by PT INKA on the 612 SS New Generation Train Unit project, two units of AC with specifications of 20,000 kCal, 10 kW are used in each carriage. The use of thisload has the potential to produce harmonic distortion in it. This research focuses on the effect of using AC on the quality of voltage and current waves that occur in K3 train carriages. The research process was carried out by taking in 3 conditions, namely without AC load, AC load, and overall load. The tools used are a Hioki CM3286-50 clamp meter and an oscilloscope. From the test results, it is known that the AC used in K3 train cars produces a THDv of 1.71% R phase, 1.67% S phase and 2.17% T phase. Meanwhile, THDi is 4.94% R phase, 6.37% S phase, and 6.79% T phase. The use of AC load does not have a significant effect on voltage harmonics but has a big effect on current harmonics which when there is no AC load produces a THDi of 59.49% R phase, 29.98% S phase, and 118.14% T phase. However, after using an AC load it produces a THDi of 4.31% R phase, 4.75% S phase, and 6.35% T phase. Because AC has a large current, the THDi value tends to be similar to AC load conditions only. It can be concluded that energysaving lamp loads containing power converter components produce higher harmonics than induction motor loads on AC. Apart from that, the THDv and IHDv values from various load conditions meet the IEEE 519-2014 standard, namely a maximum of 8% for THD and 5% for IHD. The THDi and IHDi values at full load conditions also meet IEEE 519-2014 standards, namely a maximum of 8% for TDD and 7% for IHD orders 3 to 11. Keywords: Harmonics, AC, Non-linear, Voltage, Current